PROYECTOS DE INVESTIGACIÓN Y LOS DERECHOS DE PROPIEDAD INDUSTRIAL EN LA UNIVERSIDAD PÚBLICA - CASO UNMSM - Armas Morales, Carlos (2007)
This current work has the aim of guiding San Marcos University Researchers in all issues regarding industrial copyright which are economy generators and at the same time allowers university quality accreditation and social pertinence.